Sosialisasi Sistem Pemasaran Produk Pertanian : Peluang dan Tantangan di Era Digital pada Petani Palawija Desa Ridan Permai - Tri Kurniaty; Dini Amalia Putri; Agung Pramono; Yogy Rasihen; Rahmad Akbar; Nofiar.Am, Andri (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The development of digital marketing for palawija farmers in Desa Ridan Permai is a strategic effort to enhance farmers’ competitiveness and income in facing modern market challenges. This community service activity aims to improve farmers’ understanding of utilizing digital technologies, such as social media and e-commerce platforms, as marketing tools for agricultural products. The methods employed include socialization, training, and direct assistance to farmers involving multiple stakeholders. The results show increased enthusiasm and capability among farmers in applying digital marketing, with potential to expand market reach and improve profits. However, challenges such as limited digital literacy and technology access require further attention. This program contributes significantly to supporting the transformation of local agribusiness towards a more advanced and sustainable digital era.